2006
DOI: 10.1248/cpb.54.1639
|View full text |Cite
|
Sign up to set email alerts
|

Two New Dioxopiperazine Derivatives, Arestrictins A and B, Isolated from Aspergillus restrictus and Aspergillus penicilloides

Abstract: In the course of searching for bioactive substances, two new dioxopiperazine derivatives, arestrictins A (1) and B (2), were isolated along with the known dioxopiperazine, cristatin A (3), and the known peptide, asperglucide (4), from the organic extract of the xerophilic fungi, Aspergillus restrictus and Aspergillus penicilloides. The absolute structures of 1 and 2, except for the configuration of the secondary alcohol in 1, were established by spectroscopic and chemical investigation. The absolute configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The other metabolites could be attributed to more than one genus of indoor fungi (Laatsch, 2005). The results have emphasized the presence of the metabolite asperglaucide (2270 -14600 µg/kg), potentially indicative of xerophilic fungi as A. penicillioides and A. restrictus, but also plant's metabolite (Itabashi et al, 2006;Wu et al, 2011). Anyway, the particular structural characteristics of the repository do not permit a significant air exchange with the outside and the source of asperglaucide is more likely to have fungal origin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The other metabolites could be attributed to more than one genus of indoor fungi (Laatsch, 2005). The results have emphasized the presence of the metabolite asperglaucide (2270 -14600 µg/kg), potentially indicative of xerophilic fungi as A. penicillioides and A. restrictus, but also plant's metabolite (Itabashi et al, 2006;Wu et al, 2011). Anyway, the particular structural characteristics of the repository do not permit a significant air exchange with the outside and the source of asperglaucide is more likely to have fungal origin.…”
Section: Discussionmentioning
confidence: 98%
“…known to produce sterigmatocystin, as A. versicolor and Emericella nidulans. However, very few studies have addressed methoxysterigmatocystin, and those studies were mostly concerned with contamination by A. versicolor (Klich, 2009;Nielsen et al, 1999 (Frisvad, 2015;Itabashi et al, 2006;Peterson, 2008;Tamura et al, 1999). For A. vitricola, in fact, no records were detected.…”
Section: Discussionmentioning
confidence: 99%
“…5) (Verchère et al 1969;Turner 1971;Assante et al 1979;Dorner et al 1980;Selva et al 1980;Turner and Aldridge 1983;Scheweikert 2003, Cole et al 2003;Sun et al 2012). Asperglaucide from Aspergillus restrictus and Aspergillus penicillioides (Itabashi et al 2006) has a clear resemblance to asperphenamate found in Aspergillus flavipes in subgenus Circumdati section Flavipedes (Clark et al 1977).…”
Section: Unique Extrolites In Subgenus Fumigatimentioning
confidence: 99%
“…Signals for the four protons at positions 4, 5, 6 and 7 of the indole ring were clearly observed (Table S1), and revealed that the prenyl moiety is connected to N-1 or C-2 of the indole ring. The signals of the methyl groups in the reverse prenyl moieties attached to C-2 of the indole rings of some diketopiperazine derivatives, for example, in echnulin-and isoechinulin-type alkaloids, [2][3][4] in deoxybrevianamide E [5] or okaramines, [6,7] were usually found in the range of 1.40 to 1.55 ppm. In comparison, the signals of the methyl groups in the prenyl moieties of the enzymatic products of CdpNPT are significantly up-field shifted to 0.9 to 1.1 ppm.…”
mentioning
confidence: 99%